2009
DOI: 10.1161/circulationaha.108.778688
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer of Inducible Nitric Oxide Synthase Affords Cardioprotection by Upregulating Heme Oxygenase-1 Via a Nuclear Factor-κB-Dependent Pathway

Abstract: Background-Although inducible nitric oxide synthase (iNOS) is known to impart powerful protection against myocardial infarction, the mechanism for this salubrious action remains unclear. Methods and Results-Adenovirus-mediated iNOS gene transfer in mice resulted 48 to 72 hours later in increased expression not only of iNOS protein but also of heme oxygenase (HO)-1 mRNA and protein; HO-2 protein expression did not change. iNOS gene transfer markedly reduced infarct size in wild-type mice, but this effect was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…Interestingly, disruption of COX2 and HO-1 expression did not exhibit any attenuation of the cytoprotective effect, and knockdown of NRF2 only slightly impaired the NO-induced antiapoptotic role. There are additional in vivo studies confirming that COX2 and HO-1 play important roles in NO-mediated cardioprotection (57,58). Although these molecules are up-regulated by NO in hCSCs, our results suggest that NRF2, COX2, and HO-1 may not play dominant roles in NO-mediated antiapoptosis.…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, disruption of COX2 and HO-1 expression did not exhibit any attenuation of the cytoprotective effect, and knockdown of NRF2 only slightly impaired the NO-induced antiapoptotic role. There are additional in vivo studies confirming that COX2 and HO-1 play important roles in NO-mediated cardioprotection (57,58). Although these molecules are up-regulated by NO in hCSCs, our results suggest that NRF2, COX2, and HO-1 may not play dominant roles in NO-mediated antiapoptosis.…”
Section: Discussionmentioning
confidence: 51%
“…NF-κB plays a critical role in mediating inflammatory and immune responses (13,14). Activation of NF-κB regulates an anti-apoptotic cascade and a number of anti-apoptotic genes including heme oxygenase, A20 and Bcl-2 (15,16). HO-1 is an inducible isoform produced in response to stress such as oxidative stress, hypoxia and cytokines (17).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Li and colleagues have described a functional κB element in the mouse HO-1 promoter. These authors have shown that a mechanism involving the NF-κB subunits p50 and p65 as well as the inducible NO-synthase mediated HO-1 up-regulation in vivo [85].…”
Section: Nf-bmentioning
confidence: 99%